The influence of mother's status and autonomy on the initiation of risky behavior among children - Arellano, Renee Andrea B. (School of Economics, University of the Philippines Diliman, 2018)
This study examines whether women_s status and autonomy affect the onset of risky behavior of children using data from a metropolitan area in the Philippines. Matched longitudinal data for 1,557 mothers and their children are analyzed and followed for up to 15 years. The mothers were interviewed in the year 1994 when their children were aged 9 to 11, on their status, autonomy, and sociodemographic characteristics. The children were then asked on their perception of their friends behaviors and relationship with their mothers when they were at the ages of 15-16, and 19-20 respectively. Cox proportional hazards model was used to analyze the index children_s age when they first started smoking, drinking, and taking drugs as reported by the children in 2009 at ages 25 to 26. The model demonstrated that the variables associated with women empowerment that affect the mother_child relationship are the significant factors in this study. The analysis indicates that when mothers are more educated and works for pay, children report on earlier initiation of drinking, smoking, and drug_use. This implies that in households in which mothers are not able to monitor and talk more to their children, children are more likely to engage in risky behavior earlier.